Poor Returns to Origin-Country Education for Non-Western Immigrants in Italy: An Analysis of Occupational Status on Arrival and Mobility - Fellini, Ivana (Social Inclusion, 2018)
Previous research on the Italian case has shown that non-Western immigrants are very likely to hold low-qualified jobs and that their occupational mobility chances are rather poor, which suggests low returns to education. In this paper, we investigate whether, and to what extent, immigrants’ different areas of origin moderate the returns to educational degrees obtained in the origin country. Data from a survey on the immigrant population (carried out in 2011‒2012) are used, and, differently from previous studies, we focus on returns to origin-country education with respect to both the socioeconomic status of the first job found on arrival and the subsequent occupational mobility. The results show that almost all non-Western immigrants experience remarkably low returns to post-secondary education on their first job. Contrary to other West-European countries, those returns in Italy are only slightly different by area of origin, which suggests that differences in the transferability and quality of skills are scarcely relevant in a strongly segmented labour market. Rather, the modes of labour market insertion―e.g., formal search methods or relying on contacts with natives―have a sizeable impact on the returns. Origin-country post-secondary degrees are also consistently associated with low returns on subsequent mobility, although highly educated immigrants from new EU member states experience higher chances of upward mobility. In line with some recent findings, recognition of educational credentials seems decisive for the very few non-Western immigrants who are able either to access better-qualified jobs on arrival or to improve their occupational status over time.